Fabrication and Characterization of Polyimide-CNTs hybrid membrane to enhance high performance CO2 separation - Tutuk Djoko Kusworo; Budiyono Budiyono; Ahmad Fauzi Ismail; Azeman Mustafa (International Journal of Science and Engineering, 2015)
This study investigates the CO2 separation performance of a hybrid membranes flat sheet based on polyimide incorporated with carbon nanotubes (CNTs) particles. CNTs was selected and its loading were a 1 wt% in total solid. The hybrid composite membranes were fabricated in order to increase their separation performance for the gaseous mixture of CO2 and CH4. Hybrid Composite  membrane incorporated carbon nanotubes were mannufactured  by the dry-wet phase inversion technique using flat sheet membrane casting machine system,  in which the CNTs were embedded into the polyimide membrane and the resulting membranes were characterized. The results from the FESEM, DSC and FTIR analysis confirmed that chemical modification on carbon nanotubes surface had taken place. Sieve-in-a-cage’ morphology observed shows the poor adhesion between polymer and unmodified CNT. The results revealed that the good multi-wall carbon nanotubes dispersion leads to enhanced gas permeation properties. It is also concluded that addition of carbon nanotubes particles into the matrix of Polyimide polymer has significant effect on the membrane structure and properties.